A Change of Subject: Perspectivism and Multinaturalism in Inuit Depictions of Interspecies Transformation - Desjardins, Sean (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2017)
A recurring theme within the complex cosmopolitics of pre-Christian Inuit is the transformation of persons—typically, but not exclusively, shamans (both human and nonhuman animal) and spirit beings—from one physical form, or “species,” to another. The motif is common in contemporary Inuit visual art and recent historic oral tradition, and less frequent (or less apparent) in precontact material culture. In this paper, I examine how interspecies relationships among Inuit may have been influenced by an ancient cosmology rooted in multinaturalism, which can be informed upon in an heuristic sense by Amerindian perspectivism, as described and developed by Eduardo Viveiros de Castro (1998, 2004). Within this framework, I suggest a multinatural worldview is reflected in rare depictions of interspecies transformation on two precontact Inuit artifacts recovered from the large winter village site Pingiqqalik (NgHd-1), located near Igloolik, Nunavut.